2022
DOI: 10.1002/ams2.804
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided femoral nerve block and intravenous fentanyl in pain management of the patients with hip fracture: a prospective, randomized, single blinded clinical trial

Abstract: Aim Proximal femoral fracture is a painful condition. Pain alleviation is a treatment cornerstone to both comfort the patient and reduce adverse effects. This study aimed to evaluate and compare ultrasound‐guided femoral nerve block and intravenous fentanyl administration in relieving the pain of patients with hip fractures. Methods The present interventional clinical trial was conducted on 40 patients referred to Shahid‐Bahonar Hospital with unilateral isolated proxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…Anna et al conducted a detailed postoperative follow-up on 236 elderly patients with hip fracture and found that compared with traditional drug analgesia, nerve block did not increase the incidence of adverse events in elderly hip surgery patients, which is consistent with our research results [21] . The conclusions in some other studies contradict our conclusion, and we think that this result is mainly caused by factors such as the study protocol, the method of anaesthesia, and the use of opioids [22,23,24] . During the period of this study, we did not observe any serious side effects in either patient group or side effects requiring withdrawal from this study.…”
Section: Discussioncontrasting
confidence: 97%
“…Anna et al conducted a detailed postoperative follow-up on 236 elderly patients with hip fracture and found that compared with traditional drug analgesia, nerve block did not increase the incidence of adverse events in elderly hip surgery patients, which is consistent with our research results [21] . The conclusions in some other studies contradict our conclusion, and we think that this result is mainly caused by factors such as the study protocol, the method of anaesthesia, and the use of opioids [22,23,24] . During the period of this study, we did not observe any serious side effects in either patient group or side effects requiring withdrawal from this study.…”
Section: Discussioncontrasting
confidence: 97%
“…Although previous reviews have already supported the use of ultrasound-guided preoperative nerve blocks, suggesting reduced pain, less need for opioids and a reduced risk of adverse events compared to systemic analgesia, there was no trial considered to have low risk of bias [24,25,35]. Above all, few have examined the effects of a single ultrasound-guided FNB when performed by an emergency physician [18,[26][27][28][29]. The 60% opioid reduction in the first 48h of care is similar to that of a trial evaluating the 24-hours effects of FNB performed blindly (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…through anatomical landmarks), while using it in adjunct to intravenous morphine [29]. Other trials may have been biased by the absence of randomization [18] or standardized rescue analgesia [28,29], or did not assess opioid consumption [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation